The Effect of Current Trends in Mobile Marketing on Traditional Marketing Communications and Customer Relationship Management - Hoffmann, Kristina (2011)
As consumers increasingly prefer mobile devices as their main communication and entertainment channel, it becomes more and more important for marketers as well. Mobile marketing today does not only include sending SMS and E-mail but rather is becoming a whole new interactive, rich-media marketing channel with possibilities for direct engagement with ads and brands like never before. This research attempts to provide a greater understanding about the effects of current trends in mobile marketing on traditional marketing concepts and aims to point out those concepts of the marketing strategy that can be advanced by mobile marketing. The results suggest that when mobile marketing is being implemented into an organisation’s marketing strategy, the whole marketing strategy has to be considered, with all the coherences and interrelations between different elements. Relevance and usefulness for the consumer are even more important than in any other marketing concept. Also, the danger of being intrusive has to be considered and kept in mind while designing a mobile marketing strategy.